Unilateral brachial plexus injury following carbon monoxide intoxication: A case report. Issue 30 (July 2018) - Park, Gi-Young; Kwon, Dong Rak; Jung, Won Bin
Abstract: Rationale: We report a 45-year-old male patient with unilateral brachial plexopathy following acute carbon monoxide (CO) intoxication. Patient concerns: The patient suddenly developed severe left upper extremity weakness and cognitive impairment after CO intoxication. Diagnoses: He showed severe weakness in the left upper extremity and decreased cognitive function during physical examination. Whole body bone scan revealed increased radioisotope uptake in the left shoulder, suggesting rhadomyolysis. Brain magnetic resonance imaging showed high signal intensity in both globus pallidus. The electrodiagnostic finding was compatible with incomplete left total brachial plexopathy (axonopathy). Interventions: High oxygen therapy and massive intravenous normal saline infusion were administered immediately after acute CO intoxication. Since then, intensive rehabilitation treatment has been provided. Outcome: Despite having received medical and rehabilitation treatment, the patient has not recovered severe weakness in the left upper extremity and decline in cognition. Lessons: Localized swelling in the left shoulder caused by rhabdomyolysis may be a key mechanism in developing unilateral brachial plexopathy after acute CO intoxication. The early diagnosis and treatment of rhadomyolysis might be important preventing peripheral neuropathy. An electrodiagnostic study may be helpful for diagnosis of peripheral neuropathy after CO intoxication and prediction of patient's prognosis.